2014
DOI: 10.3390/ijms150915821
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of IL-10 and TNFα on Chondrogenesis of Human Mesenchymal Stromal Cells in Three-Dimensional Cultures

Abstract: Chondrogenic differentiated mesenchymal stromal cells (MSCs) are a promising cell source for articular cartilage repair. This study was undertaken to determine the effectiveness of two three-dimensional (3D) culture systems for chondrogenic MSC differentiation in comparison to primary chondrocytes and to assess the effect of Interleukin (IL)-10 and Tumor Necrosis Factor (TNF)α on chondrogenesis by MSCs in 3D high-density (H-D) culture. MSCs were isolated from femur spongiosa, characterized using a set of typic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 70 publications
2
31
0
Order By: Relevance
“…Interpretations based on type 1 collagen staining were limited by the scaffolds nature itself (type 1/ 3 collagen composition), but there appeared a trend for less type 1 collagen especially in the co-treatment group. Similar findings have been shown by Schulze-Tanzil et al, who demonstrated an IL-10 induced COL2A1 expression in mesenchymal stem cells, that were embedded in a polyglycolic acid scaffolds 29 . Interestingly, HA biosynthesis was much more pronounced compared to aggrecan.…”
Section: Glycosaminoglycan Synthesis In Il-10 Treated Cellularized Acsupporting
confidence: 89%
See 1 more Smart Citation
“…Interpretations based on type 1 collagen staining were limited by the scaffolds nature itself (type 1/ 3 collagen composition), but there appeared a trend for less type 1 collagen especially in the co-treatment group. Similar findings have been shown by Schulze-Tanzil et al, who demonstrated an IL-10 induced COL2A1 expression in mesenchymal stem cells, that were embedded in a polyglycolic acid scaffolds 29 . Interestingly, HA biosynthesis was much more pronounced compared to aggrecan.…”
Section: Glycosaminoglycan Synthesis In Il-10 Treated Cellularized Acsupporting
confidence: 89%
“…Interestingly, joint fluid analyses revealed relatively low in vivo concentrations ranging from 1 pg/ml e 1 ng/ml after traumatic cartilage defects or OA 2,28 . Thematically related studies that directly applied IL-10 used dosages ranging from 10 to 300 ng/ml, but there is no study we are aware of that investigated dosages lower than 1 ng/ml in cartilage yet 13,15,29,30 . In addition, we could demonstrate that rising dosages of IL-10 led to reduced mRNA expression of IL-10 indicating an autocrine feedback mechanism in chondrocytes ( Fig.…”
Section: Glycosaminoglycan Synthesis In Il-10 Treated Cellularized Acmentioning
confidence: 99%
“…MSCs obtained from RA and OA patients displayed similar chondrogenic potential as MSCs isolated from healthy individuals 47 Also, MSCs isolated from bone marrow of OA patients had capacity to produce hyaline cartilage suitable for tissue repair. [66][67][68] Therefore we see no limitations in using these kinds of cells for in vitro testing of anti-inflammatory drugs.…”
Section: Oacs and Mscs In 2d Monolayer And 3d Spheroid Culturesmentioning
confidence: 99%
“…The transfection resulted in a significant increase in the chondrogenic differentiation of MSCs (Park et al, 2011). TNF-α has been also found to upregulate Sox9 gene expression (Jagielski et al, 2014). Adenovirus-mediated BMP2 and Sox9 expression in mice embryonic MSCs have shown to effectively enhance chondrogenic differentiation in vitro (Liao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%